Swi/snf alterations in squamous bladder cancers - Achenbach, Fabian; Rose, Michael; Ortiz-Brüchle, Nadina; Seillier, Lancelot; Knüchel, Ruth; Weyerer, Veronika; Hartmann, Arndt; Morsch, Ronja; Maurer, Angela; Ecke, Thorsten H.; Garczyk, Stefan; Gaisa, Nadine T. (Genes, 2020)
Dysfunction of the SWI/SNF complex has been observed in various cancers including urothelial carcinomas. However, the clinical impact of the SWI/SNF complex in squamous-differentiated bladder cancers (sq-BLCA) remains unclear. Therefore, we aimed to analyze potential expression loss and genetic alterations of (putative) key components of the SWI/SNF complex considering the co-occurrence of genetic driver mutations and PD-L1 expression as indicators for therapeutic implications. Assessment of ARID1A, SMARCA2, SMARCA4, SMARCB1/INI1, SMARCC1, SMARCC2 and PBRM1 mutations in a TCGA data set of sq-BLCA (n = 45) revealed that ARID1A was the most frequently altered SWI/SNF gene (15%) while being associated with protein downregulation. Genetic alterations and loss of ARID1A were confirmed by Targeted Next Generation Sequencing (NGS) (3/6) and immunohistochemistry (6/116). Correlation with further mutational data and PD-L1 expression revealed co-occurrence of ARID1A loss and TP53 mutations, while positive correlations with other driver mutations such as PIK3CA were not observed. Finally, a rare number of sq-BLCA samples were characterized by both ARID1A protein loss and strong PD-L1 expression suggesting a putative benefit upon immune checkpoint inhibitor therapy. Hence, for the first time, our data revealed expression loss of SWI/SNF subunits in sq-BLCA, highlighting ARID1A as a putative target of a small subgroup of patients eligible for novel therapeutic strategies.
CRIS-Team Scopus Importer:2020-12-04
Keywords: ARID1A; Immune checkpoint inhibitors; Squamous bladder cancer; SWI/SNF complex